ANALISIS PENGARUH KUALITAS LAYANAN DAN EKSTENSIFIKASI PAJAK TERHADAP KEBERHASILAN OTONOMISASI DAERAH (Studi Empiris Pada badan Pendapatan Provinsi Maluku) - Martje Ahuluheluw (Soso-Q : Jurnal Manajemen, 2020)
This study aimed at examining the influence of service quality and tax extensification on the success of regional autonomy. The population in this study were motor vehicle taxpayers at the Maluku Provincial Government. The sampling technique used was incidental sampling.The collection of primary data collection was conducted by using questionnaire (questionnaire). The number of samples collected up to the specified limit was 200, while the number of questionnaires for the data to be used was 188.Based on the analysis results, it can be concluded that service quality and tax extensification influenced the success of regional autonomy. The increasing of service quality and the success of tax extensification can affect taxpayers in carrying out their tax obligations, so that regional revenue from tax sources will increase, and will affect the success of regional autonomy. Keywords: Service quality, Regional Extensification, Success of Regional Autonomy